2023
DOI: 10.3390/bioengineering10030303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Platelet-Rich Plasma in Women with a History of Embryo Transfer Failure: A Systematic Review and Meta-Analysis with Trial Sequential Analysis

Abstract: Assisted reproductive technology (ART) is used to enhance pregnancy in infertile women. In this technique, the eggs are removed from the ovary and fertilized and injected with sperm to make embryos. Unfortunately, embryo implantation failures still occur in many of these women. Platelet-rich plasma (PRP) therapies use a patient’s own platelets to promote tissue healing and growth, including endometrium. The growth factors provided by the platelets play a criterial role on the regenerative ability of PRP. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 107 publications
0
9
0
1
Order By: Relevance
“…Intrauterine adhesions are a major complication that will cause thin endometrium. In new studies, the use of the PRP treatment after hysteroscopic adhesiolysis could decrease the intrauterine adhesion forming and improve the menstrual cycle and hypothetically the endometrial thickness and receptivity [ 45 , 46 , 47 , 48 ]. Researchers and clinicians have encountered difficulty in creating a potent therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine adhesions are a major complication that will cause thin endometrium. In new studies, the use of the PRP treatment after hysteroscopic adhesiolysis could decrease the intrauterine adhesion forming and improve the menstrual cycle and hypothetically the endometrial thickness and receptivity [ 45 , 46 , 47 , 48 ]. Researchers and clinicians have encountered difficulty in creating a potent therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests the potential benefits of PRPs in treating refractory endometrium and RIF, particularly in women with poor prognoses [45]. Recent meta-analyses and systematic reviews have shed light on the positive impact of PRPs on the improvement of the endometrial environment and RIF [46 ▪ ,47 ▪ ,48].…”
Section: Common Use Of Platelet-rich Plasmas In Reproductive Medicinementioning
confidence: 99%
“…PRP therapy is a treatment that involves the use of a patient's own blood, contains high concentration of platelets, to promote tissue regeneration 49 . In the field of assisted reproductive medicine, there have been a number of reports of intrauterine administration in patients with repeated implantation failure and thin endometrium 50–52 . Recent studies have shown that intraovarian injections of autologous PRP can enhance ovarian folliculogenesis 53,54 …”
Section: Current Treatment Of Poi For Obtaining Own Eggsmentioning
confidence: 99%
“…49 In the field of assisted reproductive medicine, there have been a number of reports of intrauterine administration in patients with repeated implantation failure and thin endometrium. [50][51][52] Recent studies have shown that intraovarian injections of autologous PRP can enhance ovarian folliculogenesis. 53,54 Cakiroglu et al initiated transvaginal PRP therapy in 311 patients with POI.…”
Section: Intra-ovarian Injection Of Prpmentioning
confidence: 99%